(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The Psychologists have noticed, not long ago, that the man’s success and happiness in life do not only depend on his degree and education, which express on his mental intelligence but also they need another kind of intelligence called emotional intelligence. The research aims at identifying the emotional intelligence level of the top and administrative leaderships in the Federal Board of Supreme Audit by evaluating their emotional intelligence when the administrative and audit leaderships face emotional interactions by dealing with administrative and audit stuffs in the Board. The research problem is focused on the following question “Is the emotional intelligence of the top and administrative leaderships in the Federal Board of Supreme Audit taken into account when they dealing with the administrative and audit stuffs”. The research submits the following hypothesis “Adopting the emotional intelligence of administrative leaderships in the Federal Board of Supreme Audit in dealing with the audit and administrative stuff will contribute to be effectiveness of audit. Therefore, to achieve the research objectives, the analytical and descriptive approach were used as well as the questionnaire was designed for that purpose and distributed to the Board’s administrative and audit leaderships. The research has reached to some conclusions, the most important of which are: the degree to which administrative and audit leaderships in Federal Board of Supreme Audit was good. This result indicates that the Board’s administrative and audit leaderships have high degree of emotional intelligence and a high ability to recognize their personal feelings and the other feelings to motivate them. They also have the ability to manage their emotions properly in relations with others. The research has reached to several recommendations such as: the administrative and audit leaderships in the Federal Board of Supreme Audit takes into account the importance of emotional intelligence role because of its moral impact on the audit process and to be part of the Federal Board of Supreme Audit’s Culture to be accepted in this Board. Thus, it will useful to achieve the required objectives.